2011
DOI: 10.1016/j.ejvs.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Perforating Veins: An Anatomical Approach to Arteriovenous Fistula Performance in the Forearm

Abstract: The cephalic vein has the fewest PVs and almost a third of them connect to the muscles. This is probably important for the maturation of the AVF, the superficial flow volume and the accessibility for puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…2E . These values of R bound the expected range for the median antebrachial vein segment near the wrist [ R = 1.3 ± 0.35 mm ( 37 )], which is used in several experiments subsequently described. The two computed curves have similar shapes but with slightly shifted values.…”
Section: Resultsmentioning
confidence: 76%
“…2E . These values of R bound the expected range for the median antebrachial vein segment near the wrist [ R = 1.3 ± 0.35 mm ( 37 )], which is used in several experiments subsequently described. The two computed curves have similar shapes but with slightly shifted values.…”
Section: Resultsmentioning
confidence: 76%
“…The novel anatomy-mapping tool CASAM [34][35][36][37] was used to visualize and evaluate the complex and variable anatomy of multiple specimens and to visualize the dissected infrapatellar branch of the saphenous nerve in one image of a knee with average dimensions. First, the knees were photographed, using a standardized protocol, with a Canon 350D camera (Canon USA, Lake Success, New York) with a Canon EF-S 18-55-mm lens (Canon USA).…”
Section: Computer-assisted Surgical Anatomy Mapping (Casam)mentioning
confidence: 99%
“…This PV is constant regarding its location and size in almost all individuals with a mean diameter of 3.6 mm, connecting the deep comitans veins with the cephalic vein in 70% and with the median cubital vein in 30% of patients. 19,20 In the absence of an AVF, we observed that blood flows in the PV from deep to the superficial venous system. In patients with a distal sWRC-AVF, we found that distribution of venous outflow is reversed through the PV to the deep venous system, limiting superficial drainage proximal to the antecubital fossa.…”
Section: Discussionmentioning
confidence: 84%